The contribution of reading interest on literature and reading comprehension toward students’ ability in writing fantasy story - Sri Endah; Harris Effendi Thahar; Yasnur Asri (International Conferences on Educational, Social Sciences and Technology)
The purpose of this research was to figure out the contribution of reading interest on literature and reading comprehension toward students’ ability in writing fantasy story of VII grade of junior high schools in Padang. This research was quantitative research that applied correlational method. The sample were 106 students. The sampling technique was stratified random sampling. Data were analyzed by using Pearson Product Moment Correlational test, multiple regression, t test, and F test. The result shown that first, the reading interest on literature contributed 61,3%. Second, the reading comprehension on fantasy story contributed 55,5%. Third, both of the reading interest on literature and reading comprehension on fantasy story contributed 63,8%. Thus, reading interest on literature and reading comprehension on fantasy story gave contribution and significant relationship toward ability in writing fantasy story text.